2017
DOI: 10.1177/1073858417702621
|View full text |Cite
|
Sign up to set email alerts
|

Graph Theory and Brain Connectivity in Alzheimer’s Disease

Abstract: This article presents a review of recent advances in neuroscience research in the specific area of brain connectivity as a potential biomarker of Alzheimer's disease with a focus on the application of graph theory. The review will begin with a brief overview of connectivity and graph theory. Then resent advances in connectivity as a biomarker for Alzheimer's disease will be presented and analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(58 citation statements)
references
References 85 publications
1
57
0
Order By: Relevance
“…At present, a growing number of neuroimaging studies have suggested that patients with SCD show atrophy of gray matter volume, degeneration of white matter fiber structure, and reduction of spontaneous functional activity in the frontal, lateral temporal, and parietal cortices ( Fan et al, 2018 ; Shu et al, 2018 ; Lin et al, 2019 ). The brain connectome, including functional connections and graph theory topological metrics, is based on functional network and has attracted increasing attention owing to the complex brain network mechanism and various diagnostic information ( Biswal et al, 2010 ; delEtoile and Adeli, 2017 ; Filippi et al, 2018 ; Gao et al, 2020 ). In a series of resting-state functional brain network researches, Wang Y. et al (2013) compared the functional connections among individuals with SCD, MCI, and normal controls (NCs) and found that the strength of the functional connection between the default mode network (DMN) and right hippocampus in the SCD group was stronger than that in the MCI group but weaker than that in the NCs.…”
Section: Introductionmentioning
confidence: 99%
“…At present, a growing number of neuroimaging studies have suggested that patients with SCD show atrophy of gray matter volume, degeneration of white matter fiber structure, and reduction of spontaneous functional activity in the frontal, lateral temporal, and parietal cortices ( Fan et al, 2018 ; Shu et al, 2018 ; Lin et al, 2019 ). The brain connectome, including functional connections and graph theory topological metrics, is based on functional network and has attracted increasing attention owing to the complex brain network mechanism and various diagnostic information ( Biswal et al, 2010 ; delEtoile and Adeli, 2017 ; Filippi et al, 2018 ; Gao et al, 2020 ). In a series of resting-state functional brain network researches, Wang Y. et al (2013) compared the functional connections among individuals with SCD, MCI, and normal controls (NCs) and found that the strength of the functional connection between the default mode network (DMN) and right hippocampus in the SCD group was stronger than that in the MCI group but weaker than that in the NCs.…”
Section: Introductionmentioning
confidence: 99%
“…3 Cognitive and behavioral symptoms in patients with dementia are considered to arise from a disruption in the neuronal interactions required for normal cognitive integration. [4][5][6] Changes in functional brain networks inferred from fMRI or PET data have been found to distinguish behavioral variant frontotemporal dementia (bvFTD) 7 from Alzheimer's disease (AD) and mild cognitive impairment (MCI) 8,9 in small studies in research settings. Similarly, longitudinal changes in MEG and EEG networks have been explored over short periods.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the graph theoretical approaches can also identify highly connected regions in a network, so-called hub nodes, which play central roles in integrating diverse information sources and supporting fast communication with minimal energy cost [11]. These network properties can be used to demonstrate fundamental aspects of normal brain organization and highlight important aspects of underlying brain pathology in various neurologic diseases such as Alzheimer disease [12], Parkinson disease [13], and epilepsy [14]. These studies have suggested that many neurologic diseases could be produced by the dysfunction of a brain network.…”
Section: Introductionmentioning
confidence: 99%